Decision-making on continuing pregnancy among Thai adolescents: A phenomenological study - Shuleeporn Prohm (2020)
© 2020, Thailand Nursing and Midwifery Council. All rights reserved. Unplanned pregnancy in adolescents often has serious difficulties for them to make decisions, whether to terminate or continue a pregnancy, whether to raise or place a baby for adoption. However, the decision-making to continuing a pregnancy among adolescents is not well conceptualized. This Heideggerian phenomenological study aimed to explain the experiences of adolescents regarding their decision-making to continue their pregnancy. The informants were 10 adolescents, who had already given birth and were residing in Chiang Mai, Thailand. Data were collected through in-depth interviews and analyzed using a 5-step interpretive process recommended by Cohen, Kahn, and Steeves. Three themes emerged: 1) challenges; 2) decision-making methods; and 3) influences on pregnancy continuation. Challenges included pregnancy unawareness and ineffective termination methods, approaching and having conflicts with supporters, focusing solely on negative aspects, and ‘should not have thought/done.’ Methods used in making decisions could be independence/firmness, compliance, discussion, supernatural powers, or indecisiveness. The decision to continue a pregnancy was influenced by unaffordability/harms of pregnancy termination, a good person, a sense of motherhood, adolescents’ conditions, and support. Nurses and midwives should incorporate these findings when providing counselling to facilitate adolescents’ decision-making.